Forgiveness: a philosophical exploration - Griswold, Charles L. (Cambridge University Press, 2007)
Forgiveness : ancient and modern -- Pardon, excuse, and forgiveness in ancient philosophy : the standpoint of perfection -- Resentment and forgiveness : Bishop Butler's seminal analysis -- Resentment -- Forgiveness -- - forgiveness at its best -- Forgiveness, revenge, and resentment -- Resentment and self-respect -- On qualifying for forgiveness: changing your ways, contrition, and regret -- On granting forgiveness: a change of heart, and seeing the offender in a new light -- The conditions of forgiveness: objections and replies -- Atonement, and the payment or dismissal of a debt -- Forgiveness as a gift, and unconditional forgiveness -- Praiseworthy conditional forgiveness -- Moral monsters and shared humanity -- Moral monsters -- Shared humanity and fallibility, compassion, and pity -- Sympathy -- The unforgivable and the unforgiven -- Forgiveness, narrative, and ideals -- Forgiveness, reconciliation, and friendship -- - imperfect forgiveness -- Ideal and non-ideal forgiveness: an inclusive or exclusive relation? -- Third party forgiveness -- Unilateral forgiveness -- Forgiving the dead -- Forgiving the unrepentant -- Self-forgiveness -- For injuries to others -- For injuries to oneself -- For injuries one could not help inflicting -- Forgiveness and moral luck -- - political apology, forgiveness, and reconciliation -- Apology and forgiveness writ large: questions and distinctions -- Political apology among the one and many -- Many to many apology: test cases -- The university of alabama and the legacy of slavery -- Apology, reparations, and the wartime internment of -- Japanese-americans -- Desmond tutu and south african churches -- A "personal" apology : king hussein in israel -- The united states senate and the victims of lynching -- One to many apology: two failures -- Robert McNamara's war and mea culpa -- Richard Nixon's resignation and pardon -- Traditional rituals of reconciliation: apology, forgiveness, or pardon? -- Apology and the unforgivable -- Apology, forgiveness, and civic reconciliation -- A culture of apology and of forgiveness : risks and abuses -- Political apology, narrative, and ideals -- Truth, memory, and reconciliation without apology -- The vietnam veterans memorial: an interpretation -- Reconciliation without apology?